Respuesta :

Answer:

f(x) = (x - 2)²

Step-by-step explanation:

f(x) = x² - 4x + 4 is a perfect trinomial.

You know a trinomial is perfect when double the square root of the first term multiplied by the square root of the last term equals the middle term.

As an equation, a trinomial in the form ax² + bx + c = 0:

2√a√c = b is a perfect trinomial.

Perfect trinomial are factored in this form:

(√a ± √c )(√a ± √c ) = (√a ± √c )²

Whether the sign is + or - depends on if the middle term is positive or negative.

In f(x) = x²-4x+4, the middle term is a negative.

The square root of the first term is 1.

The square root of the second term is 2.

The factored form is (x - 2)²

ACCESS MORE